Biotoilizer automatic system prototype : automatic fertilization system integrated with bio-toilet based on Internet of Things (IOT) - Ira Erdiandini; Rizamel Rizamel; Angelic Kusuma Nagari; Ahmad Dzakiyuddin Muhaimin; Lusi Lusi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Human urine is one of the primary wastes in urban areas, which has not been maximally processed and utilized until now. Human urine can be processed into biofertilizer with special processing procedures to minimize the negative impact of using urine as fertilizer and avoid odor, dirt, and contamination of pathogenic bacteria in the processing process. This prototype aims to design a Biotoilizer Automatic System with processing human urine into a biofertilizer and an automatic fertilization system. This system is equipped with a DC water pump, pH sensor, YL-69 sensor, ultrasonic sensor, real-time clock (RTC) NodeMCU microcontroller, and Arduino Uno. The method used in this research is an experimental method by designing technical designs and making prototypes of an Internet of Things (IoT) based automatic fertilization system that utilizes solar panels and is integrated with Bio toilets and designing software. The system's test results can process urine into a biofertilizer and fertilize automatically 95% based on regulated conditions and can be monitored with an application via a smartphone